Vitamin D as a risk factor for patient survival after kidney transplantation: A prospective observational cohort study. Issue 5 (28th March 2019) - Thorsen, Inga S.; Bleskestad, Inger H.; Åsberg, Anders; Hartmann, Anders; Skadberg, Øyvind; Brede, Cato; Ueland, Thor; Pasch, Andreas; Reisæter, Anna V.; Gøransson, Lasse G.
Abstract: Background: Short‐term survival after kidney transplantation is excellent, but long‐term survival remains low and is equivalent to non‐end‐stage renal disease patients with many invasive malignancies. The aim of the study was to explore vitamin D status in the early phase after transplantation as a prognostic marker for long‐term graft and patient survival. Methods: All first‐time kidney transplant recipients between October 2007 and October 2012 in Norway were included. Vitamin D was measured 10 weeks post‐transplant. Information on graft failure and death was obtained from the Norwegian Renal Registry. Results: Seven hundred and sixty‐two first‐time kidney transplant recipients were included, with a median age of 57 years and a median follow‐up of 82 months. In the follow‐up period, there were 172 graft failures (23%) and 118 deaths (15%). Eighty‐six percent of the transplant recipients with sufficient vitamin D levels were alive with a well‐functioning graft after 5 years using Kaplan‐Meier survival estimates, compared with 79% and 76% of the patients with vitamin D deficiency and insufficiency, respectively ( P = 0.006). Conclusion: In a nation‐wide cohort of 762 first‐time kidney transplant recipients, long‐term graft and patient survival were better in recipients with vitamin D sufficiency 10 weeks post‐transplant compared with those with vitamin D deficiency and insufficiency.